Financial development and international trade : is there a link? - Beck, Thorsten, 1967- 1967- (Policy research working paper, 2001)
Economies with better developed financial sectors have a comparative advantage in manufacturing industries. A two-sector model shows the sector with large scale economies profiting more than the other from a well-developed financial sector. In countries with higher levels of financial development, manufactured exports represent a higher share of GDP and of merchandise exports, and those countries have a higher trade balance in manufactured goods